Advances Concepts for Intelligent Vision Systems 13th International Conference, ACIVS 2011, Ghent, Belgium, August 22-25, 2011. Proceedings - Blanc-Talon, Jacques; Kleihorst, Richard; Philips, Wilfried; Popescu, Dan; Scheunders, Paul (Lecture Notes in Computer Science, 2011)
This book constitutes the refereed proceedings of the 13th International Conference on Advanced Concepts for Intelligent Vision Systems, ACIVS 2011, held in Ghent, Belgium, in August 2011. The 66 revised full papers presented were carefully reviewed and selected from 124 submissions. The papers are organized in topical sections on classification recognition, and tracking, segmentation, images analysis,  image processing, video surveillance and biometrics, algorithms and optimization; and 3D, depth and scene understanding.